The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/00207543.2015.1061224
|View full text |Cite
|
Sign up to set email alerts
|

Responding to supplier temporary price discounts in a supply chain through ordering and pricing decisions

Abstract: This paper considers a one-retailer and one-supplier supply chain and addresses the question of how a retailer should use its ordering and pricing decisions to respond to its supplier's temporary price discounts. The paper considers a hybrid environment -somewhere between deterministic and stochastic modelling approaches -that is, the retailer does not know when the next promotion from its supplier will occur but, once the promotion is announced, all its details are deterministic and often there is some time r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…When the discounts are moderate, it is the strongest. Xia [13] studied a supply chain with only one retailer and supplier and addressed how retailers should use their ordering and price decisions to respond to temporary price discounts from their suppliers. Gao et al [14] established a dualchannel supply chain model, studied the impact of price discounts on the bullwhip effect in e-commerce, and found that price discounts in online retail markets generally amplify the bullwhip effect in the retail supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the discounts are moderate, it is the strongest. Xia [13] studied a supply chain with only one retailer and supplier and addressed how retailers should use their ordering and price decisions to respond to temporary price discounts from their suppliers. Gao et al [14] established a dualchannel supply chain model, studied the impact of price discounts on the bullwhip effect in e-commerce, and found that price discounts in online retail markets generally amplify the bullwhip effect in the retail supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Raju [3] first found that the increase in discount range would increase the variability of category sales, while the increase in discount frequency would have the opposite effect. Xia [4] solved the problem of how the retailer used ordering and pricing decision to respond to supplier's temporary price discount. Cai et al [5] analyzed three models: supplier Stackelberg, retailer Stackelberg, and Nash game, and found that considering price discount not only could bring more profits but also reduced channel conflicts in the supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on these basic models, integrated decisions on ordering and pricing are investigated under different settings Discrete Dynamics in Nature and Society 3 and perspectives, such as product return [2,28], supply uncertainty [29], service level constraint [30,31], multiple price markdowns [32], supply chain contracts [33,34], dual sourcing channel [35,36], and multiperiod planning [3,37,38]. Other creative works include the research on joint ordering and pricing decisions considering repeat-purchase based on the Bass model [39], retailer's ordering and pricing decisions of responding to the supplier's temporary price discounts [40], ordering and pricing model considering transshipment between two independent retailers [41], and retailer's joint ordering, pricing and advertising decisions [42].…”
Section: Integrated Decisions On Operations and Marketingmentioning
confidence: 99%